Triplet repeat RNA structure and its role as pathogenic agent and therapeutic target - Krzyzosiak, Wlodzimierz J. (Oxford University Press, 2012)
This review presents detailed information about the structure of triplet repeat RNA and addresses the simple sequence repeats of normal and expanded lengths in the context of the physiological and pathogenic roles played in human cells. First, we discuss the occurrence and frequency of various trinucleotide repeats in transcripts and classify them according to the propensity to form RNA structures of different architectures and stabilities. We show that repeats capable of forming hairpin structures are overrepresented in exons, which implies that they may have important functions. We further describe long triplet repeat RNA as a pathogenic agent by presenting human neurological diseases caused by triplet repeat expansions in which mutant RNA gains a toxic function. Prominent examples of these diseases include myotonic dystrophy type 1 and fragile X-associated tremor ataxia syndrome, which are triggered by mutant CUG and CGG repeats, respectively. In addition, we discuss RNA-mediated pathogenesis in polyglutamine disorders such as Huntington's disease and spinocerebellar ataxia type 3, in which expanded CAG repeats may act as an auxiliary toxic agent. Finally, triplet repeat RNA is presented as a therapeutic target. We describe various concepts and approaches aimed at the selective inhibition of mutant transcript activity in experimental therapies developed for repeat-associated diseases.